Pengaruh Social Media Influencer dan Pengetahuan Keuangan Tehadap Minat Investasi Mahasiswa Di Pasar Modal - Intan Mutmainah Harun; Mohamad Agus Salim Monoarfa; Meriyana Franssisca Dungga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Financial Influencers and Financial Literacy on Investment Interest in the Capital Market, focusing on students of the Faculty of Economics and Business, Universitas Negeri Gorontalo. The sampling technique applied in this study is Slovin’s formula, which results in a total sample of 100 respondents. The data collection method utilized primary data by distributing questionnaires. The analysis method in this study is multiple linear regression analysis. The result of this study show that partially financial influencers have a significant influence on investment interest. This indicates that the presence of influencers can motivate and attract students to invest. However, financial literacy has no significant influence on investment interest, implying that student’s level of understanding and knowledge about investment does not influence their interest in investing. Simultaneously, financial influencers and financial literacy influence investment interest, with a determination coefficient of 23.8%, while the remaining 76.2% is influenced by other variables not examined in this study.